Warm Ambient Temperature Decreases Food Intake in a Simulated Office Setting: A Pilot Randomized Controlled Trial - Bernhard, Molly C.; Li, Peng; Allison, David B.; Gohlke, Julia M. (Frontiers in Nutrition, 2015)
Background We hypothesized that exposure to temperatures above the thermoneutral zone (TNZ) would decrease food intake in young adults in a sedentary office environment over a 2-h period. Methods Participants wearing standardized clothing were randomized to perform routine office work in the TNZ, considered control (19–20°C), or above the TNZ considered warmer (26–27°C) using a parallel-group design (n = 11 and 9, respectively). Thermal images of the inner canthus of their eye and middle finger nail bed, representing proxies of core and peripheral temperatures, respectively, were taken at baseline, first, and second hour during this lunchtime study. Heat dissipation was estimated using peripheral temperature. General linear models were built to examine the effects of thermal treatment on caloric intake and potential mediation by heat dissipation. Researchers conducted the trial registered as NCT02386891 at Clinicaltrials.gov during April to May 2014. Results During the 2-h stay in different ambient temperatures, the participants in the control conditions ate 99.5 kcal more than those in the warmer conditions; however, the difference was not statistically significant. Female participants ate about 350 kcal less than the male participants (p = 0.024) in both groups and there was no significant association between caloric intake and participant’s body mass index (BMI). After controlling for thermal treatment, gender and BMI, the participant’s peripheral temperature was significantly associated with caloric intake (p = 0.002), suggesting a mediating effect. Specifically, for every 1°C increase in peripheral temperature suggesting increased heat dissipation, participants ate 85.9 kcal less food. Conclusion This pilot study provided preliminary evidence of effects of thermal environment on food intake. It suggests that decreased food intake in the experimental (warmer) environment is potentially mediated through thermoregulatory mechanisms.